Deciphering the initiation mechanism of Yersinia outer protein secretion - Mustafa, Nour (My University, 2024)
Bacteria have evolved intricate secretion systems to enhance pathogenicity and survival, with the Type III Secretion System (T3SS) being a key virulence factor in many pathogens. This thesis investigates the binding interactions between the YscXY chaperone-substrate complex and the YscV gate protein in Yersinia, employing techniques such as protein analysis and cryo-electron microscopy. Contrary to previous studies, our findings demonstrate that the C-terminal region of YscX is not essential for binding to YscV, suggesting alternative binding mechanisms. Additionally, we uncovered significant impacts of storage conditions on protein oligomerization states, with fresh GST-YscVc displaying a more complex oligomerization behavior compared to frozen samples. The Δ50 mutation in YscX promoted higher-order oligomerization, indicating a regulatory role for the N-terminal region.Cryo-EM analysis achieved a resolution of 2.93 Å, sufficient to interpret side-chain positions in the rigid regions of the protein. This map provides detailed structural insights and highlights the importance of specific regions in the protein complex. Future steps include further refinement of this map and exploring potential conformational changes during secretion. These insights contribute to a deeper understanding of T3SS dynamics, offering potential targets for therapeutic intervention to mitigate bacterial virulence.
Keywords: Type III Secretion System, Protein-Protein Interaction, Protein Secretion, YscV, YscY Chaperone, YscX Effector Protein, Single-Particle Cryo-EM